(untitled) (Research, Society and Development, 2022)
Objective: To analyze the advantages and disadvantages of Ozempic for the treatment of obesity. Methods: Through an integrative analysis, it was possible to highlight different investigations in scientific articles. The article established inclusion criteria, such as keywords, publication language and being on one of the preselected platforms (Scielo, PubMed and RDU) and also established exclusion criteria, such as incomplete research, was the subject investigated and without methods and explicit methods. Results: The Ozempic (semaglutide) has good results in helping to lose weight in obese patients. Despite being developed for the treatment of patients with type 2 diabetes mellitus, the results for obesity were positive. Among the main results is weight loss, which is directly conditioned to the dosage of medication, as well as a better energy intake and a lower preference for fatty foods in the patients’ choice. All these factors were considered advantages. Among the disadvantages of using the drug is the fact that it is new in the market, which limits scientific research. According to the authors, some researchers have already established a causal relationship between the use of semaglutide and thyroid cancer in rodents; this factor has not been proven in humans and is considered a disadvantage. Final considerations: The use of Ozempic presents interesting results for weight loss, however, although the long-term side effects of the use of this drug are not known, a factor that may pose a risk to patients who are using Ozempic for it. treatment of obesity.